SOSIALISASI : PERAN LEMBAGA MAHASISWA DAN KARANG TARUNA SEBAGAI PENGAWASAN PARTISIPATIF DALAM MENGAWAL PILKADA SERENTAK TAHUN 2024 YANG BERINTEGRITAS DAN DEMOKRATIS - Daholu, Ahmad; Hasni, Hasni; Rilan, La (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The 2024 Simultaneous Regional Head Election (PILKADA) is a means of popular sovereignty to elect the Governor and deputy governor, Regent and Deputy Regent, Mayor and deputy mayor, which is carried out directly, publicly, freely, confidentially, honestly and fairly. This service research uses a qualitative descriptive analysis approach method. The results of this socialization show an active increase in participatory supervision by participants, namely youth, students and youth organizations in monitoring and supervising the stages of the regional elections, namely by using the strategy of inviting other youth friends in the form of millennial voters or beginner voters or voters. women's base not to get involved in money politics and not get involved in spreading regional election hoaxes on social media or other media. Because of the massive black campaign and indications of money political movements, it is certain that it will harm the dignity of democracy. With strict participatory supervision, fraud in elections such as money politics, vote manipulation and voter intimidation can be minimized, as well as ensuring an honest and fair election process.